African Digital Research Repositories: Mapping the Landscape [preprint] - Havemann, Jo; De Mutiis, Anna; Bezuidenhout, Louise; Owango, Joy; Kitchen, Stephanie (My University, 2020)
The International African Institute (IAI, https://www.internationalafricaninstitute.org) in collaboration with AfricarXiv (https://info.africarxiv.org) present an interactive map of African digital research literature repositories. This drew from IAI’s earlier work from 2016 onwards to identify and list Africa-based institutional repositories that focused on identifying repositories based in African university libraries. Our earlier resources are available at https://www.internationalafricaninstitute.org/repositories. The interactive map extends the work of the IAI to include organizational, governmental and international repositories. It also maps the interactions between research repositories. In this dataset, we focus on institutional repositories for scholarly works, as defined by Wikipedia contributors (March 2020)
Keywords: research repository; open access; Africa